Processo de criação da música pop e expansão dos registros de processo: o caso Let it Be - The Beatles - Cappellano, Ana Paula (2010)
The following dissertation intends to investigate the creative process of pop music from the study of the audiovisual format as a musical creative process register, the documentary film and the making of in particular. Relations and interactions between the music created in the music industry dynamics and the culture of the image, as well as with the expansion of the registers and documents of process of music, from the eletronic record to the video, are established. Pop music refers to that of the Culture Industry, of media insertion, especially mass media, such as the radio, the cinema and the television, and their production is seen as a wide creative network. The documentary Let it Be, by the British group The Beatles, filmed in 1969 and released in 1970, was chosen as case study and, from the processes critique approach and based on the theories of the work of art creative networks, by Cecília Almeida Salles, it is understood as register and index of the collective process of creation of the band. The movie is considered, from this perspective, a precursor of the audiovisual format known today as the making of and, based on their critical analysis, different moments and points of tension are recognised during the creation and recording of an album, nods of the pop music network. We seek to understand how the interactions among their members, the creative subjects, as well as with external factors to that specific process, characterized the collective process of creation of the group at that stage of their career